Has agricultural intensification impacted maize root traits and rhizosphere interactions related to organic N acquisition?. Issue 4 (19th June 2020) - Schmidt, Jennifer E; Poret-Peterson, Amisha; Lowry, Carolyn J; Gaudin, Amélie C M
Abstract: Plant–microbe interactions in the rhizosphere influence rates of organic matter mineralization and nutrient cycling that are critical to sustainable agricultural productivity. Agricultural intensification, particularly the introduction of synthetic fertilizer in the USA, altered the abundance and dominant forms of nitrogen (N), a critical plant nutrient, potentially imposing selection pressure on plant traits and plant–microbe interactions regulating N cycling and acquisition. We hypothesized that maize adaptation to synthetic N fertilization altered root functional traits and rhizosphere microbial nutrient cycling, reducing maize ability to acquire N from organic sources. Six maize genotypes released pre-fertilizer (1936, 1939, 1942) or post-fertilizer (1984, 1994, 2015) were grown in rhizoboxes containing patches of 15 N-labelled clover/vetch residue. Multivariate approaches did not identify architectural traits that strongly and consistently predicted rhizosphere processes, though metrics of root morphological plasticity were linked to carbon- and N-cycling enzyme activities. Root traits, potential activities of extracellular enzymes (BG, LAP, NAG, urease), abundances of N-cycling genes ( amoA, narG, nirK, nirS, nosZ ) and uptake of organic N did not differ between eras of release despite substantial variation among genotypes and replicates. Thus, agricultural intensification does not appear to have impaired N cycling and acquisition from organic sources by modern maize and its rhizobiome. Improved mechanistic understanding of rhizosphere processes and their response to selective pressures will contribute greatly to rhizosphere engineering for sustainable agriculture. Abstract : Synthetic nitrogen (N) fertilizers have fundamentally changed the availability of this critically important plant nutrient in agricultural systems, replacing organic sources such as compost and cover crops. Decades of plant breeding have created maize varieties that are highly productive under synthetic nitrogen fertilization, but potential trade-offs for uptake of organic nitrogen were unclear. Using a small panel of maize genotypes, we find minimal impacts of modern breeding on maize root traits, interactions between roots and associated microorganisms that regulate organic matter breakdown and transformations, and uptake of organic nitrogen from cover crops.